An uncertainty model of a non-ideal open area test site for electromagnetic measurement - Wibowo, Ignatius Agung (2018)
An open area test site (OATS) is a standard facility to perform electromagnetic compatibility (EMC) compliance testing of electrical and electronic products. An ideal OATS is a flat area, free of any obstructions and external signals. Precompliance testing in a non-ideal OATS is an economical way to prepare a product for compliance testing. However, measurements in the non-ideal OATS have higher uncertainty. In addition, the existing model to analyse the measurement uncertainty is not adequate. Therefore, this research proposes an uncertainty model of a non-ideal OATS for electromagnetic measurement to analyse the measurement uncertainty components in the non-ideal OATS. In this research a normalized site attenuation (NSA) measurement uncertainty model was derived. A 3-m non-ideal OATS has been designed and built. The suitability of the location to build the OATS has been evaluated. To evaluate the measurement uncertainty in the site and the closeness of the site NSA to the ideal NSA, a series of NSA measurements in the non-ideal OATS were performed in the frequency range of 300 MHz to 1000 MHz. From the analysis, the expanded uncertainties of the OATS with a coverage factor of 2 were in the range of ±1.68 dB to ±1.98 dB. Besides, the OATS NSA values were inside ±4 dB margins as specified in CISPR 16-1-4:2010 standard. Therefore, the non-ideal OATS is eligible for pre-compliance testing. Based on many factors investigated in the sensitivity analysis, it was found that the dominant factor that contributed to the measurement uncertainty in the non-ideal OATS came from the antennas. In summary, this research mainly contributes to the development and evaluation of a low cost non-ideal OATS for pre-compliance testing.